Inside Back Cover: Volume 3 Issue 3. Issue 3 (24th August 2022) - Qiu, Jiajia; Zhao, Huaping; Lei, Yong
Abstract : Inside back cover image : Electrode design and optimization of micro‐supercapacitors (MSCs) is of great significance among the multitudes of strategies for boosting energy density without jeopardizing power density and cycle life, especially considering the limited footprint area of MSCs. This review categorizes and arranges the emerging "smart" design strategies of electrodes into three design concepts: layer‐by‐layer, scaffold‐assisted and rolling origami. The corresponding strengths, the challenges and the potential solutions are comprehensively inventoried. The smart design principle of electrodes for the next‐generation of high‐performance MSCs and key perspectives for future research in this field are outlined. (DOI: 10.1002/smm2.1094 )